Protection of Interests of Children: The Roles of Religions and Legal Regimes - Adebayo, Akintunde Abidemi (Brawijaya Law Journal, 2020)
Religion provides the basis for the protection of human rights, namely, right to life, dignity of human person, right to property, among others. Without prejudice or disrespect to other religions, this paper focuses on Christianity religion and protection of rights of children considering their vulnerability. To this end, the Holy Bible provides for measures to safeguard, protect and ensure the good as well proper upbringing of children. Similarly, the United Nations Convention on the Rights of the Child, OAU Charter on the Rights and Welfare of the Child and the Child Rights Act provide for protection of rights of children. The essence of these provisions is to ensure the smooth running of the society and betterment of humanity. Therefore, this paper examines the salient provisions to safeguard and protect rights and interests of children in Christianity as well as under the aforementioned legal regimes. It concludes that while not undermining the significant role of laws in the protection of rights of children, religion plays an augmenting role of protecting the interests of children by instilling in members of the society, the needed respect for humanity and morality which is mostly lacking in the modern era. It recommends among other things that, government at all levels as well as religious leaders should give priority attention to the protection of children.